A COMPARATIVE CORPUS IN NEWS ARTICLES DISCOURSE ON THE DEATH OF HIS MAJESTY THE KING OF THAILAND - Chansri, Natthicha; Lamjuanjit, Yuttachak (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 4 No 3 (2567): กันยายน-ธันวาคม 2567, 2024)
The present study was undertaken to facilitate comprehension of the ideological content conveyed through the lexical elements present in texts. Because ideology is embedded in language, discourses used in newspapers construct a narrow ideological perspective for the readers to interpret subjects and events. On the basis of news articles from The Bangkok Post, The Nation, The BBC, and The CNN that associated with His Majesty the King Bhumibol Aduljadet, the study investigated which discourses and keywords associated with His Majesty the King Bhumibol Aduljadet occurred frequently in each newspaper. Findings suggested that a keyword analysis pointed to frequent discourses on emotion in The Bangkok Post and The Nation, and on politics in The BBC and CNN. Because of their ideological differences, the newspapers constructed a reality, surprisingly; the subject was presented in very different ways.